Intercalibration of the Hb3gr 40Ar/39Ar dating standard. - Jourdan, Fred; Verati, C.; Feraud, G. (Elsevier Science BV, 2006)
The 40Ar/39Ar dating technique is based on the knowledge of the age of neutron fluence monitors (standards). Recent investigations have improved the accuracy and precision of the ages of most of the Phanerozoic-aged standards (e.g. Fish Canyon Tuff sanidine (FCs), Alder Creek sanidine, GA1550 biotite and LP-6 biotite); however, no specific study has been undertaken on the older standards (i.e. Hb3gr hornblende and NL-25 hornblende) generally used to date Precambrian, high Ca/K, and/or meteoritic rocks.In this study, we show that Hb3gr hornblende is relatively homogenous in age, composition (Ca/K) and atmospheric contamination at the single grain level. The mean standard deviation of the 40Ar/39ArK (F-value) derived from this study is 0.49%, comparable to the most homogeneous standards. The intercalibration factor (which allows direct comparison between standards) between Hb3gr and FCs is RFCsHb3gr = 51.945 0.167. Using an age of 28.02 Ma for FCs, the age of Hb3gr derived from the R-value is 1073.6 5.3 Ma (1σ, internal error only) and 8.8 Ma (including all sources of error). This age is indistinguishable within uncertainty from the K/Ar age previously reported at 1072 11 Ma [Turner G., Huneke, J.C., Podosek, F.A., Wasserburg, G.J., 1971. 40Ar-39Ar ages and cosmic ray exposure ages of Apollo 14 samples. Earth Planet. Sci. Lett. 12, 19-35]. The R-value determined in this study can also be used to intercalibrate FCs if we consider the K/Ar date of 1072 Ma as a reference age for Hb3gr. We derive an age of 27.95 0.19 Ma (1σ, internal error only) for FCs which is in agreement with the previous determinations. Altogether, this shows that Hb3gr is a suitable standard for 40Ar/39Ar geochronology.